HIV Status Disclosure and Quality of Life of People Living with HIV/AIDS in the Ho Municipality, Ghana. (24th November 2022) - Agbeko, Adams; Owusu, Richard; Alhassan, Yakubu; Letsa, Timothy; Axame, Wisdom Kudzo; Ogum-Alangea, Deda
Abstract : Background . Quality of life (QoL) and HIV/AIDS serostatus disclosure are vital HIV outcome indicators. This study examined factors associated with QoL, HIV status disclosure, and the relationship between QoL and disclosure among people living with HIV (PLWHIV) at the Ho Teaching Hospital. Methods . We conducted a hospital-based cross-sectional survey among 311 PLWHIV. The World Health Organization WHOQOL-HIV BREF questionnaire was used to measure QoL. A semistructured questionnaire was used to gather information on socio-demographics and HIV serostatus disclosure. Multivariate logistic and multiple linear regressions were used to determine predictors of HIV serostatus disclosure and QoL in six domains, respectively. Results . Overall, 88.7% of participants disclosed their HIV status to a significant relation. The majority (98.1%) presented with good QoL, high (83.3%) among participants who disclosed their HIV seropositive status. Patients on antiretroviral therapy (ART) for more than a year were 8.64 times more likely to disclose their HIV status as compared to those on ART for less than a year (AOR = 8.64 (95% CI: 2.00–37.27), p = 0.004 ). Increasing years on ART ( β  = 0.37) and being employed ( β  = 1.31) positively predicted good QoL in the physical domain, whereas higher educational level positively predicted good QoL in the social domain ( β  = 0.66). QoL was not associated with HIV serostatus disclosure. Conclusion . HIV status disclosure was high. Increasing years on ART increased the odds of disclosure. Although there was no significant relationship between QoL and disclosure, good QoL was high among those who disclosed their HIV status. Increasing years on ART, higher education, and being employed predicted good QoL.